Perspectives of proteomic analysis in ophthalmology - A.A. Krylova; A.V. Zakharchuk; O.I. Krivosheina; S.I. Pekov; I.A. Popov (РМЖ "Клиническая офтальмология")
A.A. Krylova1, A.V. Zakharchuk1, O.I. Krivosheina1, S.I. Pekov2,3, I.A. Popov1,3 1Siberian State Medical University, Tomsk, Russian Federation 2Skolkovo Institute of Science and Technologies, Skolkovo, Russian Federation 3Moscow Institute of Physics and Technology, Moscow, Russian Federation This paper reviews the perspectives of proteomic analysis of tear and aqueous humor to determine biomarkers for the differential diagnosis of eye disorders. The methodology of sample collection and the advantages and disadvantages of the available methods are discussed in detail. The results of proteomic mapping of tear and aqueous humor in dry eye disease, keratoconus, glaucoma, cataract, age-related macular degeneration, and diabetic retinopathy are described. The association between the levels of identified proteins and their role in triggering pathological processes, e.g., oxidative stress with autophagy (and, as a result, tissue dystrophy), initiation of inflammation, and impairment of metabolic processes at the molecular level with activation of pathological proteolysis (that ultimately lead to cellular and tissue changes with the development of the above-mentioned diseases) are of particular importance. This paper also emphasizes the practical relevance of using proteomics to study the pathogenesis of eye diseases, which implies determining the association between genotype and phenotype of a patient in clinical practice with further treatment personalization. Proteomics also provides an early noninvasive diagnosis of socially significant eye diseases. Keywords: proteomic analysis, tear, aqueous humor, mass spectrometry, eye disorders. For citation: Krylova A.A., Zakharchuk A.V., Krivosheina O.I., Pekov S.I., Popov I.A. Perspectives of proteomic analysis in ophthalmology. Russian Journal of Clinical Ophthalmology. 2023;23(4):213–218 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-7.